Unpacking Identity Dynamics of the Main Character in the Novel Kimchi Confessions: Implications for Multicultural Education - Nukha, Afifa Ulin; Amilia, Fitri; Dzarna, Dzarna; Mijianti, Yerry (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The identity dynamics of a main character in a novel refer to how their sense of self, values, beliefs, and overall identity evolve throughout the narrative. These dynamics are shaped by psychological, emotional, and social factors, which influence how the character perceives themselves and is perceived by others. This process often occurs in response to the conflicts, experiences, or challenges the character faces. In literature, such transformations serve as powerful tools for examining broader societal themes, such as belonging, cultural assimilation, and personal growth. This research aims to analyze the identity dynamics of the main character in Kimchi Confessions by Xaviera Putri, exploring its implications for multicultural education in Indonesia. Employing a qualitative research method, this study uses a descriptive analysis approach to gain a deep understanding of the main character's identity development. The data source for this study is Kimchi Confessions, a novel inspired by Xaviera Putri’s personal experiences living in South Korea during her high school years. Published in 2023 by Gagas Media, the novel spans 200 pages. Data analysis is conducted using a discourse analysis approach to identify how the main character’s identity is represented throughout the narrative. The findings reveal that Xaviera’s experiences emphasize the importance of multicultural education in promoting cross-cultural understanding and inclusivity in Indonesia. This study highlights how literature can serve as a tool for fostering empathy and cultural awareness, suggesting that further research into identity dynamics in contemporary literature can enhance educational practices and societal integration.